Supplier Selection And Evaluation In Food Manufacturing Sector - Nurul Farhana Ilias (OUM, 2021)
Many organizations invest a lot in ensuring efficient supply selection and have come up with various criteria to ensure that the process of supplier selection is efficient, flawless, and can result in value-adding outcomes. However, very often, many organizations tend to encounter problems when it comes to selecting suppliers that are competent enough to supply it with what it needs. Hence, this leads to the generation of the main objective of this study to examine the supplier selection criteria and evaluation towards the food industry sector, from 3 different dimensions, including economic, environmental, and social dimensions. The research methodology was developed to answer the research question in this study via 4 phases, which include problem identification, literature review, framework development, and validation and verification. Through an identified rating scale, the performance of the supplier was determined by the respondents via the scores they provided. From the data analysis shown, the suppliers are expected to fulfil the criteria of the rating score which is expected achie At the end of the research, the researcher can conclude that economic sustainability, social sustainability, and environmental sustainability were very important sustainability- based factors that need to be given attention to when engaged in the process of choosing suppliers. The suggestion that the procurement department will focus effortson ensuring that the suppliers they choose to become their partners in the supply chainare able to exhibit the required and accepted levels of economic, social, and environmental sustainability.